2014
DOI: 10.1093/jac/dku453
|View full text |Cite
|
Sign up to set email alerts
|

Daptomycin in paediatrics: current knowledge and the need for future research

Abstract: To overcome the problems stemming from antimicrobial resistance, there have been several attempts to develop new antimicrobials in recent years. Of the highly potent drugs targeting resistant Gram-positive bacteria, daptomycin has a number of attractive characteristics that suggest its possible use in the treatment of serious infections due to these organisms. Although several pharmacokinetic and clinical studies in adults have provided data to determine how this drug should be prescribed to obtain the maximal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 46 publications
0
14
0
4
Order By: Relevance
“…This and its once-daily administration make it an attractive therapeutic option for infections caused by these pathogens. 16 EU-CORE was initiated to capture real-world data regarding the use of daptomycin in the treatment of Gram-positive infections. The results from this analysis showed that children and adolescent patients with a variety of Gram-positive infections treated with daptomycin had a high clinical success rate, whether daptomycin was used as first- or second-line therapy.…”
Section: Discussionmentioning
confidence: 99%
“…This and its once-daily administration make it an attractive therapeutic option for infections caused by these pathogens. 16 EU-CORE was initiated to capture real-world data regarding the use of daptomycin in the treatment of Gram-positive infections. The results from this analysis showed that children and adolescent patients with a variety of Gram-positive infections treated with daptomycin had a high clinical success rate, whether daptomycin was used as first- or second-line therapy.…”
Section: Discussionmentioning
confidence: 99%
“…10 Higher doses may be required in younger patients and the administration of 15 mg/kg/12 h was reported as a maximum dose in the literature in an infant. 2,8 Our patient was treated at a dose of 8 mg/kg/ Serum CPK levels were in normal limits during the treatment. On 3th, 9th and 13th days after completion of daptomycin treatment the blood cultures were persistently negative.…”
Section: Case Reportmentioning
confidence: 97%
“…Moreover, drug dosage, safety and tolerability have not been definitely established in children. 2 We report our experience about treatment of a VRE bacteremia in a 3-yearold boy with acute myeloid leukemia (AML)-M7 and Down syndrome.…”
Section: Vancomycin-resistant Enterococcus Bacteremia In a Child Withmentioning
confidence: 99%
See 1 more Smart Citation
“…Daptomycin is currently not approved for use in the pediatric population, and appropriate dosages for pediatric patients of different ages are yet to be clearly defined. 85 A pharmacokinetic study in 25 children (2–17 years of age) receiving 4 mg/kg/day of daptomycin showed a more rapid clearance in those younger than 6 years. 86 Another study conducted later showed that use of high-dose (8–10 mg/kg/day) daptomycin in children aged 2–6 years provided systemic exposure comparable to that seen in adults treated with the approved daptomycin doses of 4–6 mg/kg/day.…”
Section: Daptomycin Use In Pediatric Patientsmentioning
confidence: 99%